Social media use and parent–child relationship: A cross‐sectional study of adolescents. Issue 3 (28th November 2019) - Sampasa‐Kanyinga, Hugues; Goldfield, Gary S.; Kingsbury, Mila; Clayborne, Zahra; Colman, Ian
Abstract: We examined the association between social media use and parent–child relationship quality and tested whether this association is independent of total screen time. Data on 9, 732 students (48.4% female) aged 11–20 years were obtained from a provincially representative school‐based survey. Heavy use of social media (daily use of more than 2 hr) was associated with greater odds of negative relationships between mother–daughter (odds ratio [OR] = 1.79; 95% confidence interval [CI]: 1.27–2.52), father–daughter (OR = 1.56; 95% CI: 1.16–2.09), father–son (OR = 2.19; 95% CI: 1.58–3.05) but not mother–son (OR = 1.17; 95% CI: 0.88–1.55). Results were similar after further adjusting for total screen time. There were no significant associations between regular use of social media (2 hr or less) and parent–child relationships. These findings suggest that heavy use of social media is associated with negative parent–child relationships. Longitudinal research is necessary to disentangle the pathways between social media use and the parent–child relationship.